Quality and performance evaluation metrics of websites : a systematic literature review - AL Dulaimi, Abdullah; Al- Mashhadany, Shayma (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Background - Websites play an important role in government, educational and commercial organizations. In the field of education, using websites of universities has been increased and because of that it has been importance to ensure that the universities have an effective websites. Various metrics have been used to evaluate the quality of websites. All these metrics affect the performance and quality of website . Objectives - This paper presented a systematic literature review SLR to get an overview about the current studies of distinct criteria for evaluating the websites and each criteria is explored briefly to give the basic idea behind it. In general, the paper’s objective is to give an up-to-date introduction and short review of these criteria . Methods – A Systematic literature review is implemented according to the guidelines of performing a SLR in software engineering. The study was based on a comprehensive set of papers gathered from the online libraries published within time span 2010 to 2022 . Conclusions - The results from this SLR include information about the criteria for evaluating the quality and performance of the multi-level web according to previous research, which was divided into applicable sub-criteria, and then the latter was divided into measurable indicators. within a specific period that can help researchers in this field through providing an overview of the current researches in this area. Furthermore, it may serve as a first step towards a great explanation of the topic with the help of SLR .